Potency of xanthone derivatives as antibacterial agent against Methicillin-Resistant Staphylococcus Aureus (MRSA) - Isnatin Miladiyah; Farida Juliantina Rachmawaty (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Antibiotic resistance is increasing worldwide and becoming a serious problem for the treatment of patients and also affecting their economy. One instance of bacteria that is resistant to the antibiotic is Methicillin- Resistant Staphylococcus aureus (MRSA). MRSA infections are fatal and even deadly. Some MRSA strain has shown resistance towards currently available antibacterial agents. To overcome this, we need new compound alternatives. One of the compounds currently being developed is xanthone derivatives. Xanthones can be found in many kinds of plants, including Garcinia mangostana , in which the active compounds are mangostanin and ±-mangostin. Xanthones is effective against several types of Grampositive and Gram-negative bacterias, including Staphylococcus species. Some studies have shown that xanthone derivatives are effective against Staphylococcus aureus, including MRSA. One of the proposed mechanisms of xanthone's antibacterial activity is the involvement of the bacteria's cytoplasmic membrane. Xanthone amphiphilic compounds are capable of disrupting bacterial membrane through a mechanism called interfacial activity models. Xanthone can also act as the antioxidant and by inducing the release of lipoteichoic acid (LTA) from the cell wall of MRSA. LTA is the main constituent of the cell wall of Gram-positive bacteria, which are covalently bonded to the outside of peptidoglycan. This structure is important for cell division and bacterial osmotic protection. Thus, it is believed that the mechanism of action of xanthones involved damaging bacterial cell membrane.